Academic Management System Integration Of Private Universities - Suryadi; Mulyani, Sri; Gaffar, Mohammad Fakry; Komariah, Aan; Suhendar, Ade; Rusnati, Ius; Wulansari, Sri (Publisher Cv. Inara, 2021)
The Academic Management System of Higher Education is a component of the Institutional Management System of Higher Education, which is concerned with the overall management tools that have been designed and compiled in a systematic and rigorous manner. Nowadays, as technology advances and student generations change, educational institutions are encouraged to continually respond to the use of technology in their service systems. The aim of this thesis is to identify and interpret research results relating to academic management system alignment. A descriptive qualitative approach is used in this research. According to the findings of the study, while universities do have an institutional management scheme in place, its execution is not optimal. Universities do have an Academic Management System in place, but it is not yet fully implemented. The academic Management System also has some elements missing, such as academic calendar scheduling, new student placement, new and old student enrollment, classes, grading, thesis instruction, and graduation. Keywords: Academic Management System, Technology, universities.